2016
DOI: 10.1016/j.jcrysgro.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the optical quality and energy resolution of CsSrBr3: Eu scintillator crystals

Abstract: The crystal growth of CsSrBr 3 : Eu with improved energy resolution for use in gammaray detection applications is reported. CsSrBr 3 boules doped with 5% Eu were grown by the vertical Bridgman method in quartz ampoules of 17 mm and 22 mm diameter. It was observed 10 that the addition of an excess of CsBr in the melt improved the optical transparency and energy 11 resolution of the scintillator crystals. The energy resolution of the gamma-ray spectra recorded 12 with crystals measuring ø 22 mm × 15 mm was 7.4% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The crystal sample is not fully transparent, which indicates that the crystal quality can be further improved by optimizing the crystal growth condition. A similar result was also observed for CsSrBr 3 crystals, (29) Gokhale et al suggested that the poor optical quality may be caused by the volatilization of CsBr during synthesis and crystal growth. Thus the poor optical transparency of the grown CsSrCl 3 :Ce crystal may be due to the volatilization of CsCl during the crystal growth process.…”
Section: Resultssupporting
confidence: 71%
“…The crystal sample is not fully transparent, which indicates that the crystal quality can be further improved by optimizing the crystal growth condition. A similar result was also observed for CsSrBr 3 crystals, (29) Gokhale et al suggested that the poor optical quality may be caused by the volatilization of CsBr during synthesis and crystal growth. Thus the poor optical transparency of the grown CsSrCl 3 :Ce crystal may be due to the volatilization of CsCl during the crystal growth process.…”
Section: Resultssupporting
confidence: 71%
“…CsSrBr3 is a wide-band gap white orthorhombic halide perovskite that is used as a scintillator when doped with rare earth ions. 36,37 Compared to the 2.29(2) eV band gap of pure CsPbBr3, replacing 75% of the Pb 2+ cations with Sr 2+ increases the band gap by 350 meV to 2.64(3) eV. Pure phase CsSrBr3 has a band gap beyond the visible regime, so it is colorless because it does not significantly absorb visible light.…”
Section: Straus and Cavamentioning
confidence: 99%
“…These results demonstrate that homovalent B-site alloying is a viable strategy to continuously tune the band gap of halide perovskites, which may enable optical applications where it is necessary to dial in the precise band gap of a material. 36…”
Section: Straus and Cavamentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the melts based on mixed halides of alkali and alkaline earth metals, it should be noted that they are used for the growth of crystals of new promising scintillation materials activated with europium(II), which usually possesses high scintillation efficiency. [1][2][3][4] Alkaline earth metal halides are used as one of the components of such matrixes for the simplification of the activator entering into the crystalline lattice of the matrix because of complete or partial isomorphism of Eu 2+ cation and Ca 2+ , Sr 2+ , Ba 2+ cations. Since the radii of Eu 2+ and Sr 2+ cations are almost equal (0.132 and 0.131 nm, respectively 5 ), matrixes on the basis of strontium halides are a priori the most promising ones.…”
Section: Introductionmentioning
confidence: 99%